Dislocation as Graced Opportunity: Theology for a Synodal Church - Lennan, Richard (Theological studies, 2024)
Large-scale and widespread social and ecclesial upheaval results in the experience of “dislocation,” a feeling of homelessness flowing from the loss of certainty and stability. This article considers how dislocation might provide an opening to creativity and hope, especially in the life of the ecclesial community. Synodality can be an instance of such creativity and hope, even though, paradoxically, synodality itself can be a catalyst for dislocation. To make its case for synodality, the article highlights the church’s eschatological orientation, its graced pilgrimage of faith.